Widespread contamination of SARS‐CoV‐2 on highly touched surfaces in Brazil during the second wave of the COVID‐19 pandemic. (20th January 2022) - da Silva, Severino Jefferson Ribeiro; do Nascimento, Jessica Catarine Frutuoso; dos Santos Reis, Wendell Palôma Maria; da Silva, Caroline Targino Alves; da Silva, Poliana Gomes; Mendes, Renata Pessôa Germano; Mendonça, Allyson Andrade; Santos, Bárbara Nazly Rodrigues; de Magalhães, Jurandy Júnior Ferraz; Kohl, Alain; Pena, Lindomar
Summary: Although SARS‐CoV‐2 surface contamination has been investigated in health care settings, little is known about the SARS‐CoV‐2 surface contamination in public urban areas, particularly in tropical countries. Here, we investigated the presence of SARS‐CoV‐2 on high‐touch surfaces in a large city in Brazil, one of the most affected countries by the COVID‐19 pandemic in the world. A total of 400 surface samples were collected in February 2021 in the City of Recife, Northeastern Brazil. A total of 97 samples (24.2%) tested positive for SARS‐CoV‐2 by RT‐qPCR using the CDC‐USA protocol. All the collection sites, except one (18/19, 94.7%) had at least one environmental surface sample contaminated. SARS‐CoV‐2 positivity was higher in public transport terminals (47/84, 55.9%), followed by health care units (26/84, 30.9%), beach areas (4/21, 19.0%), public parks (14/105, 13.3%), supply centre (2/21, 9.5%), and public markets (4/85, 4.7%). Toilets, ATMs, handrails, playgrounds and outdoor gyms were identified as fomites with the highest rates of SARS‐CoV‐2 detection. Taken together, our data provide a real‐world picture of SARS‐CoV‐2 dispersion in highly populated tropical areas and identify critical control points that need to be targeted to break SARS‐CoV‐2 transmission chains.